The Fidelity of Implementation and Teachers’ Perceptions of the SIMPLE Approach: Evidence from Lower Secondary Classrooms in Kosovo - Morina, Qendresa; Vondrová, Naďa (Scientia in educatione, 2025)
This study is part of broader research focused on the SIMPLE Approach, a constructivist intervention that integrates the bar model method with metacognitive scaffolding to enhance word problem-solving skills in Kosovo's lower secondary classrooms. It specifically examines the fidelity of implementation and teachers' perceptions of this approach. The study aims to fill a research gap in design-based intervention studies, which recognise the critical role of teachers but provide limited insight into their actual work and how faithfully they implement interventions. To address this gap, the study explored two areas: (1) the fidelity of three teachers' implementation of the SIMPLE Approach and (2) the teachers' perceptions of its usefulness. Data collected from classroom observations, teacher diaries, and interviews revealed varying levels of fidelity, which improved over time. Teacher 1 exhibited the lowest fidelity, struggling with the bar model method and limiting group work. In contrast, Teacher 3 demonstrated the highest fidelity, successfully incorporating all aspects of the SIMPLE Approach and promoting active pupil engagement. Regarding their perceptions, all three teachers maintained positive attitudes towards the SIMPLE Approach from the outset and appreciated its benefits by the end of the intervention. Although the generalisability of the findings is limited, they suggest that the SIMPLE Approach holds promise. However, the study highlights the need for comprehensive teacher training and ongoing support, especially when introducing new methods, to ensure effective implementation and high fidelity.